A survey of socio-economic disparities between the regions of the EU - Daniel Moucque (EIB Papers, 2000)
The European Union is facing challenges that have important implications for its economy as a whole and for regional cohesion in particular. The transition to the euro had already started, as had the process of enlargement towards Central and Eastern European countries. This occurs against a backdrop of increasing globalisation and a second industrial revolution based on information technology. The current essay consequently surveys the resulting social and economic trends in the regions. Section 2 finds that there is a clear distinction between a successful, prosperous and competitive EU core and regions, often in the periphery, which perform less well. Section 3 briefly surveys the factors that underlie competitiveness, and suggests that the main reasons for poor performance can be found in unfavourable sectoral structures, a lack of innovative capacity, poor accessibility and low education. The situation in Eastern Europe is discussed in Section 4. Finally, Section 5 summarises and concludes.
Keywords: 330; Regionale Disparität; Entwicklungskonvergenz; Regionale Arbeitslosigkeit; EU-Staaten